Management of retained placenta in patient with valvular heart disease with pulmonary edema (Health Renaissance, 2013)
A case of retained placenta following full-term vaginal delivery with an unscarred uterus where surgical management of delivering the placenta was not attempted due to unfavorable cardiac condition is presented. Although she was planned for hysterectomy, she was successfully managed medically with injection methotrexate. Health Renaissance, January-April 2013; Vol. 11 No.1; 83-85 DOI: http://dx.doi.org/10.3126/hren.v11i1.7608